An Autonomous Security Validation Architecture for Linux Systems in Regulated Financial Environments - Balaramakrishna Alti (International Journal of Intelligent Systems and Applications in Engineering, 2025)
Linux systems are widely deployed across regulated financial environments to support critical workloads such as transaction processing, customer data management, risk analytics, and regulatory reporting. These systems must continuously comply with stringent security and regulatory requirements while accommodating frequent operational changes driven by patching, configuration updates, and incident response. Traditional security validation approaches, which rely on periodic audits and manual assessments, provide only point-in-time assurance and struggle to maintain visibility into security posture in dynamic environments. This paper presents an autonomous security validation architecture for Linux systems operating in regulated financial environments. The proposed architecture combines declarative security control definitions, continuous runtime validation, and autonomous analysis components to assess security posture without relying solely on manual intervention. Validation processes continuously compare observed system state against approved security baselines, while autonomous analysis identifies recurring validation failures, correlates deviations across systems, and prioritizes risks based on regulatory and operational impact. The architecture is designed to support autonomy in validation and analysis while preserving explainability, auditability, and human oversighted requirements in regulated financial contexts. Through architectural design and controlled evaluation in enterprise Linux environments aligned with financial regulatory expectations, the study demonstrates that autonomous security validation improves detection timeliness, reduces configuration drift, and strengthens compliance readiness. The findings indicate that autonomous validation architectures can enhance security assurance in regulated environments when implemented with appropriate governance controls. <!–StartFragment –>DOI: https://doi.org/10.17762/ijisae.v13i1s.7986<!–EndFragment –>